The makings of a man: social generational masculinities in Bangladesh. Issue 3 (3rd April 2018) - Hasan, Md Kamrul; Aggleton, Peter; Persson, Asha
Abstract: The emergence of specific forms of masculinity is bounded by space and time. While attention has been given to the contexts within which forms of masculinity develop, rather less is known about men's enactment of masculinity from a social generational perspective. To address this gap, insights from Mannheim's work on social generations, and Connell's notions of masculinity are drawn upon to advance understanding of social generational masculinities in modern-day Bangladesh. A multi-site cross-sectional study was conducted in three cities, using interviews to elicit narratives of masculinity from 34 men of three social generations: an older generation (aged 53–75 years and growing up in the 1950s and 1960s), a middle generation (aged 30–46 years and growing up in the 1980s), and a younger generation (aged 19–27 and growing up post-1995). Thematic analysis was used to identify key notions around what it meant to be a man. While all men subscribed to the view that 'real' men should be providers, they differed by social generation with respect to perspectives on work, religion and sexuality. Historical, economic and cultural changes across the generations have shaped these differences, highlighting the importance of a social generational perspective for understanding masculinities in Bangladesh.